Opium and bladder cancer: A systematic review and meta-analysis of the odds ratios for opium use and the risk of bladder cancer. - Mahdi Afshari; Ghasem Janbabaei; Mohammad Amin Bahrami; Mahmood Moosazadeh (PLoS ONE)
Objective The association between opium use and bladder cancer has been investigated in many studies, with varying reporting results reported. This study aims to estimate the total odds ratio for the association between bladder cancer and opium consumption using meta-analysis. Methods The study was designed according to PRISMA guidelines. Two independent researchers searched for the relevant studies using PubMed, Web of Science, Scopus, OVID, Embase, and Google Scholar. After systematic screening of the studies identified during the first step, Cochrane risk of bias tool was determined for the selected studies. The case-control and the cohort studies were investigated to assess risk of bladder cancer due to opium use. In addition, the cross-sectional studies were analysed separately to assess frequency of opium consumption. These estimates were combined using the inverse variance method. Fixed or random effect models were applied to combine the point odds ratios. The heterogeneity between the primary results was assessed using the Cochran test and I-square index. The suspected factors for heterogeneity were investigated using meta-regression models. An Egger test was conducted to identify any probable publication bias. Forest plots illustrated the point and pooled estimates. All analyses were performed using Stata version 14 software and RevMan version 5.3. Results We included 17 primary studies (11 case-control, one cohort and five cross-sectional) in the final meta-analysis. The total odds ratios (95% confidence intervals) for developing bladder cancer by opium use alone, and concurrent use of opium and cigarettes were estimated as 3.85 (3.05-4.87) and 5.7 (1.9-16.3) respectively. The odds ratio (95% confidence interval) for opium use with or without cigarette smoking was estimated as 5.3 (3.6-7.7). Conclusion This meta-analysis showed that opium use similar to cigarette smoking and maybe with similar mechanisms can be a risk factor for bladder cancer. It is therefore expected to be a risk factor for other cancers.